The concept of leadership and constitution from the Islamic and Malay archipelago perspectives according to Taj Al Salatin manuscript - Suhaimy, Khairul Azman; Nordin, Shah Rul Anuar; Othman, Hussain; Jaes, Lutfan; Kamri, Khairol Anuar; Damin, Zahrul Akmal; Halim, Harliana; Abdul Rahim, Mohd Hisyam; Borham, Abdul Shakor; Mubarak, Mohd Zain; Ismail, Marwan; Othman, Mohd Fuad; et al. (Science Publishing Corporation (SPC), 2018)
The aspect of leadership has existed since the dawn of time, with scholars conducting extensive studies from various angles and views, which were then produced into literary works. In the Malay Archipelago, Taj al-Salatin manuscript (1603M) is widely known as a masterpiece which highlighted leadership qualities from the Islamic perspective. This study was conducted to identify the author‟s ideas on Islamic leadership in the context of Malay Archipelago, using descriptive method by analysing the manuscript. The findings showed that leaders and leadership are considered as a mandate from Allah S.W.T. Good leaders must be qualified, with higher knowledge and morals than their subjects. Taj al-Salatin introduces the idea that leaders should practice Tasawwuf, which among its practises include constant self reminder of death, rejecting lust and desires, and prioritising remembrance to Allah. In his manuscript, Bukhari al-Jauhari presents the vision, idealism and the idea of "leaders are perfect beings", which embodies the concept of Tauhid and upholds noble character for universal humanity. A leader of a nation should always stand on the grounds of good moral values and the people are led towards creating a peaceful, prosperous and happy nation.